Match 'em right!: a card game to learn malay and english proverbs / Norasyikin Abdul Malik ... [et al.] - Abdul Malik, Norasyikin; Hasni, Nurul Ain; Ya Shak, Mohamad Syafiq; Megat Abdul Rahim, Puteri Rohani (2020)
Figurative speech is a common way to deliver one's thought to another in everyday conversation. The beauty of language lies on these figurative idioms, proverbs which reflects the spiritual treasures of language of the people and culture. People use proverbs, idioms, sarcasm, irony, hyperbole, metaphor, simile, metonymy, teasing, and puns in their speech for various aspects of lives and purpose. However, when one tries to use it in another language other than their mother tongue, complication and confusion might occur as most second language (L2) or foreign language (FL) speakers are not familiar with the proverbs of the referred language. Most of them will opt for direct translation of the native language proverbs instead of using the proverbs of the language they speak with similar meaning. As Johnson (2006) explained that games offer a meaningful context for learning, Match 'em Right was crafted to help these L2 and FL speakers to not only experience the excitement of game playing but also enrich their knowledge of the language and culture that they are learning or speaking. A few studies revealed that when proverbs are taught in the classroom, they can enrich knowledge of one's cultural and literary understanding. However, second language learners face difficulty in understanding English proverbs. Based from an initial investigation conducted to study students' knowledge in identifying the English proverbs that have similar meaning with the Malay proverbs, reveals that majority of the students failed to know the right English proverbs of the Malay proverbs that they know. Some of them don't even know the meaning of the Malay proverbs even though they have heard them before.